Equity Research of Vodafone Group PLC - Santos Simões, João; Krabec, Tomáš, 1981-; Husák, Martin; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2024)
The aim of this thesis is to understand and analyze Vodafone Group Plc business and provide a recommendation for an investor. From the analysis, the investor for Vodafone would be a combination of a value investor and an income investor. The current stock price, which stands at its lowest point in the past two decades, coupled with assessments derived from discounted cash flow (DCF) and market multiples valuation methods, unequivocally indicate that the stock is significantly undervalued and possesses strong fundamentals, aligning well with the principles of value investing. Additionally, Vodafone's consistent payment of semiannual dividends, which rank among the highest on the FTSE index, makes it particularly appealing to income-oriented investors seeking stable returns.
Vedoucí práce: Tomáš Krabec
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses